Pulmonary arterial pruning is associated with CT-derived bronchiectasis progression in smokers. (October 2022) - Dolliver, Wojciech R.; Wang, Wei; Nardelli, Pietro; Rahaghi, Farbod N.; Orejas, Jose L.; Maselli, Diego J.; Yen, Andrew; Young, Kendra; Kinney, Gregory; Estépar, Raul San José; Diaz, Alejandro A.
Abstract: Loss of small pulmonary arteries measured as the ratio of blood vessel volume in arteries <5 mm 2 in cross-section to total arterial blood vessel volume (BV5a/TBVa), with lower values indicating more pruning, was associated with 5-yr progressing CT-derived bronchiectasis in smokers (Odds Ratio (OR) [95% Confidence interval], 1.28 [1.07–1.53] per 5% lower BV5a/TBVa, P = 0.007). Corresponding results in smokers with COPD were: OR 1.45 [1.11–1.89] per 5% lower BV5a/TBVa, P = 0.007. The results support a vascular factor for structural progression of bronchiectasis. Highlights: It is known that bronchiectasis presents with a loss of small pulmonary vessels. In this study, a loss of small pulmonary arteries was associated with structural bronchiectasis progression. A vascular factor might play a role in structural bronchiectasis progression.